Repurchase Intention Conditioned to Economic Confidence in Main Street Retail Districts - Eliane Tanabe Deliberali; Marcelo Moll Brandão; Flávio Santino Bizarrias (BBR: Brazilian Business Review)
The crisis of confidence in Brazil creates a scenario that can influence relations between the attributes of the retailer and consumers. Consumer assessments can be adjusted to economic confidence, leading to more utilitarian values or decreasing the hedonic value of buying experiences. Thus, it is necessary to understand the intervention of economic confidence in the responses of consumers to the attractiveness factors of a retail cluster. We conducted an analysis on the extent to which attribute assessments and crowding perception, hedonic and utility value, and satisfaction, interact with economic confidence, and satisfaction to influence performance and repurchase intention. A survey was carried out in the purchase environment with 300 consumers (region of Rua 25 de Março, São Paulo). Hypotheses were tested by PLS and Process. The mediating role of the economic trust between hedonic value and satisfaction was evidenced, proving adjustment of the hedonic value with the decrease of confidence. Theoretical and practical contributions are discussed in the conclusions.